2014
DOI: 10.1071/an14345
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions and feeding behaviour of feedlot cattle supplemented with nitrate or urea

Abstract: Nitrate may serve as a non-protein nitrogen (NPN) source in ruminant diets while also reducing enteric methane emissions. A study was undertaken to quantify methane emissions of cattle when nitrate replaced urea in a high concentrate diet. Twenty Angus steers were allocated to two treatment groups and acclimated to one of two iso-energetic and iso-nitrogenous finisher rations (containing NPN as urea or as calcium nitrate), with all individual feeding events recorded. A single methane measurement device (C-lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Ramin and Huhtanen, 2013) they match observed data (MY 13.6 g/kg DMI) for similar concentrate diets (Hegarty et al, 2007) and with these same 24 animals measured in respiration chambers on the same diet (MY 15.5 g/kg DMI; Herd et al, unpublished data) 2 months later. The accuracy of using GEM has been shown (Velazco et al, 2014) through comparison with respiration chambers, so there is no reason to doubt the accuracy of the GEM as the CO 2 recoveries were high (95.9% and 97.9% of the gravimetrically determined quantities of CO 2 released into the shroud were recovered by the two GEM units used in the experiment). All model methane estimates and the average of spot estimates were lower than those predicted for feedlot cattle using Moe and Tyrell (1979).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramin and Huhtanen, 2013) they match observed data (MY 13.6 g/kg DMI) for similar concentrate diets (Hegarty et al, 2007) and with these same 24 animals measured in respiration chambers on the same diet (MY 15.5 g/kg DMI; Herd et al, unpublished data) 2 months later. The accuracy of using GEM has been shown (Velazco et al, 2014) through comparison with respiration chambers, so there is no reason to doubt the accuracy of the GEM as the CO 2 recoveries were high (95.9% and 97.9% of the gravimetrically determined quantities of CO 2 released into the shroud were recovered by the two GEM units used in the experiment). All model methane estimates and the average of spot estimates were lower than those predicted for feedlot cattle using Moe and Tyrell (1979).…”
Section: Resultsmentioning
confidence: 99%
“…Jonker et al, 2014). Velazco et al (2014) supplemented cattle with nitrate and reported unexpected DMP results using the GreenFeed emission monitoring (GEM) system that coincided with differences in time interval between feeding and GEM measurement, which may have skewed the estimates of DMP. This finding stimulated a more intensive examination of the relationship between DMP and feeding history of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that nitrate-fed steers consumed more meals per day, resulting in a shorter time interval between consuming a meal and having methane measured by the GreenFeed system. Velazco et al (2014) concluded that there was a need for caution in extrapolating 'short-term emission measures', as are obtained by the GreenFeed system, to daily methane-emission rates. This need for caution when employing the GreenFeed system was also recently echoed by Hammond et al (2015).…”
Section: Measurement Of Methane Emissionsmentioning
confidence: 99%
“…There have been no Australian studies on dairy cows using the GreenFeed system. However, Velazco et al (2014) compared the methane emissions from Angus steers fed diets supplemented with either nitrate or urea. They reported that nitrate-fed steers consumed more meals per day, resulting in a shorter time interval between consuming a meal and having methane measured by the GreenFeed system.…”
Section: Measurement Of Methane Emissionsmentioning
confidence: 99%
“…MitiGate currently contains data from 412 sheep, beef and dairy cattle publications. The eight largest published beef MY datasets with all data needed for metaanalyses are from Herd et al (2014), Richmond et al (2015), Rooke et al (2014), McGinn et al (2009), Eugène et al (2011), Fitzsimons et al (2013), Boadi et al (2004) and Velazco et al (2014). Most of these datasets were missing from the MitiGate database at the time of our study, but were included in the metaanalysis presented in the current paper.…”
Section: Introductionmentioning
confidence: 99%